2020
DOI: 10.1007/s00109-020-01992-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the novel SARS-CoV-2 by quantitative RT-PCR: variations and opportunities

Abstract: The world is currently facing a novel viral pandemic (SARS-CoV-2), and large-scale testing is central to decision-making for the design of effective policies and control strategies to minimize its impact on the global population. However, testing for the presence of the virus is a major bottleneck in tracking the spreading of the disease. Given its adaptability regarding the nucleotide sequence of target regions, RT-qPCR is a strong ally to reveal the rapid geographical spreading of novel viruses. We assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 65 publications
0
40
0
1
Order By: Relevance
“…Moreover, the nucleotide mutation rate reported for SARS‐CoV‐2 was 8E‐04 substitution per site per year 13,14 . Many studies have already shown the high evolution rate of SAR‐CoV‐2 in many cases and linked its evolution with its origin 5 . Detection methods using RT‐PCR are based on a fixed target, however, as the pandemic proceeds the virus is changing and many cases are missed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the nucleotide mutation rate reported for SARS‐CoV‐2 was 8E‐04 substitution per site per year 13,14 . Many studies have already shown the high evolution rate of SAR‐CoV‐2 in many cases and linked its evolution with its origin 5 . Detection methods using RT‐PCR are based on a fixed target, however, as the pandemic proceeds the virus is changing and many cases are missed.…”
Section: Discussionmentioning
confidence: 99%
“…These measurements rely on an accurate diagnosis of individuals infected with the virus by using real‐time reverse‐transcriptase polymerase chain reaction (RT‐PCR) 4 . The most common targets for detecting SARS‐CoV‐2 by (RT‐PCR) assays in diagnostic laboratories are the ORF1ab gene, the RdRP gene, the E gene, the N gene, and the S gene 5 …”
Section: Introductionmentioning
confidence: 99%
“…In very severe cases, the disease can progress rapidly and become complicated by acute respiratory distress syndrome (ARDS) and coagulopathies 11 . To date, it is recommended that the definitive diagnosis of SARS-CoV-2 infection be confirmed by a positive RT-PCR test or genetic sequencing 12 .…”
Section: Discussionmentioning
confidence: 99%
“…This RT-qPCR is currently a reliable test commonly used for the diagnosis of SARS-CoV-2 infected symptomatic and asymptomatic patients [56]. Several scientific and clinical institutions around the world have produced molecular assays to diagnose SARS-CoV-2 and have made RT-qPCR primers and sample sets available to the public [57].…”
Section: Recent Development Of Rt-pcr For Sars-cov-2 Diagnosismentioning
confidence: 99%
“…As the genetic code of coronaviruses consists of RNA, its purification of the test samples is a crucial step in RT-qPCR protocols. Officially, institutions in some countries have suggested unique RNA isolation kits for SARSCoV-2 detection [57]. Various virus extraction and detections kits are available in market as shown in Table 3.…”
Section: Recent Development Of Rt-pcr For Sars-cov-2 Diagnosismentioning
confidence: 99%